Innovative house structures for malaria vector control in Nampula district, Mozambique: assessing mosquito entry prevention, indoor comfort, and community acceptance - Francisco, Micanaldo Ernesto; Watanabe, Kozo (Frontiers in Public Health, 2024)
Background: Insecticide-treated mosquito bed nets and indoor residual spraying are widely used for malaria vector control. However, their effectiveness can be affected by household members' habits, requiring alternative approaches toward malaria vector control.Objective: To assess the effectiveness of modified houses in preventing mosquito entry; to assess the impact of house modifications on indoor air conditions and evaluate the acceptability of modified houses in the community where the study was conducted. Methods: Five traditional and five modified houses were constructed in Nampula district, Mozambique and underwent a 90-day overnight indoor mosquito collection using Centers for Disease Control and nitride ultraviolet light traps during the rainy season. Mosquitoes were identified morphologically. Indoor temperature, relative humidity, carbon dioxide levels and wind speed were also collected. The Student's t-test was used to compare the means of the number of mosquitos and environmental factors between both house types. A binomial form of the Generalized Linear Model identified the factors associated with the community volunteer's preference for house type.Results: Modified houses reduced the number of Anopheles by an average of 14.97 mosquitos (95% CI, 11.38 to 18.56, p<0.000) and non-Anopheles by 16.66 mosquitoes (95% CI, 8.23 to 25.09, p<0.000). Although fewer mosquitoes were trapped in modified houses compared to traditional ones, the modifications were more effective against Anopheles (94% reduction) than for non-Anopheles (71% reduction). The average temperature increased at 0.25C in modified houses but was not statistically significant (95% CI, (-0.62 to 0.12 p = 0.181). Community volunteers preferred modified houses due to reduced mosquito buzzing. The efficacy of modified houses including its acceptability by community, highlight its potential to lower malaria risk.Effective integration of modified houses into the vector control strategy will require raising awareness among communities about malaria risks associated with house structure and training them to modify their houses.